New Bilevel Model to Enhance Optimal Interaction between Retailer and Customers Based on the Multiobjective Robust Approach in the Energy Market - Kourosh Apornak; Soodabeh Soleymani; Faramarz Faghihi; Babak Mozafari (International Transactions on Electrical Energy Systems)
In electricity markets, the optimal management of buying and selling energy is achieved based on the correct interaction of players. This study proposes a multiobjective bilevel model for optimal decision making of retailer based on interactions with selected customers and wholesalers with appropriate environmental performance in electricity market contracts. In this regard, at the upper level, the retailer’s first objective which is profit maximization is realized, while at the lower level, the objective of minimizing customer costs is achieved. Also, the second goal of the retailer is to buy more energy from wholesalers with better environmental performance. For the presented model, in order to properly model the uncertainty of the generation capacity of wholesalers, the robust optimization approach (ROA) has been used. Finally, the mixed integer linear programming (MILP) based on McCormick’s linearization method and Karush–Kuhn–Tucker conditions will be solved by CPLEX solver in GAMS software. The final results show the optimal decision of the retailer in choosing customers with the aim of maximizing profit so that the selected customers also pay the minimum cost for the purchased energy.